Sustainable catalysis with fluxional acridine-based PNP pincer complexes. Issue 23 (2nd March 2022) - Kar, Sayan; Milstein, David
Abstract : The recent developments of sustainable catalytic reactions catalyzed by fluxional acridine-based PNP pincer complexes are explored, focusing on their unique structural features and reactivities compared to other traditional pincer complexes. Abstract : Because of the widespread use of fossil fuels and the resulting global warming, development of sustainable catalytic transformations is now more important than ever to obtain our desired fuels and building materials with the least carbon footprint and waste production. Many sustainable (de)hydrogenation reactions, including CO2 reduction, H2 carrier systems, and others, have been reported using molecular pincer complexes. A specific subset of pincer complexes containing a central acridine donor with flanking CH2 PR2 ligands, known as acridine-based PNP pincer complexes, exhibit special reactivities that are not imitable by other PNP pincer complexes such as pyridine-based or (R2 PCH2 CH2 )2 NH type ligands. The goal of this article is to highlight the unique reactivities of acridine-based complexes and then investigate how these reactivities allow these complexes to catalyse many sustainable reactions that traditional pincer complexes cannot catalyse. To that end, we will initially go over the synthesis and structural features of acridine complexes, such as the labile coordination of the central N donor and the observed fac – mer fluxionality. Following that, distinct reactivity patterns of acridine-based complexes including their reactivity with acids and water will be discussed. Finally, we will discuss the reaction systems that have been developed with acridine complexes thus far, including the notable selective transformations of primary alcohols to primary amines using ammonia, N-heteroaromatic synthesis from alcohols and ammonia, oxidation reactions with water with H2 liberation, development of H2 carrier systems, and others, and conclude the article with future possible directions. We hope that the systemic study presented here will aid researchers in developing further sustainable reactions based on the unique acridine-based pincer complexes.